DUKUNGAN PERKEMBANGAN DAN PERILAKU EKONOMI ANAK USIA DINI DI PAUD EKLESIA ANGKASA, KOTA JAYAPURA, PAPUA - Elsyan Rienette Marlissa; Herlina Irianti Mulyono; Nickanor Kaladius Reumi Wonatorey; Vince Tebay; Westim Ratang; Gregorius Adista Enrico Astawa; Ferdinant Martinus Djawa; Ulfah Rizky Muslimin (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service activity is titled “Supporting the Development and Economic Behavior of Early Childhood at PAUD Eklesia Angkasa, Jayapura City, Papua.” The program is based on the importance of introducing economic concepts from an early age, particularly related to needs, scarcity, and wise resource management. Early childhood education focuses not only on academic aspects but also on character building and the development of basic economic understanding relevant to daily life. This activity aims to equip PAUD teachers with the skills to teach economic concepts in a simple, creative, and contextual manner. The program involved teachers, church administrators, and the Kingmi Eklesia Angkasa Foundation. The roles of parents, teachers, and the church are crucial in instilling values such as hard work, responsibility, discipline, and proper financial management based on Christian principles from an early age. The materials delivered include understanding needs and wants, saving habits, learning through play, and the ability to set priorities. The main objective is to enhance teachers’ knowledge and participants’ understanding in supporting the development of children’s economic behavior effectively and sustainably. The results indicate an improvement in teachers’ ability to teach basic economic concepts to children. Additionally, the program encourages children to develop discipline, appreciate effort, and manage their needs wisely. Collaboration among teachers, parents, and the community plays a significant role in shaping positive character traits that will benefit children in their future lives.